1993
DOI: 10.1007/bf00025086
|View full text |Cite
|
Sign up to set email alerts
|

Genotypical differences in responses to iron deficiency between sensitive and resistant cultivars of chickpea (Cicer arietinum)

Abstract: Differences in responses to iron deficiency between two chickpea cultivars, NP-62 and K-850, were examined. The apical leaves of NP-62 quickly showed symptoms of iron-deficiency chlorosis when grown on an iron-free medium. By contrast, K-850 showed no visible symptoms on the same medium. Iron contents of the apical leaves of these two cultivars were similar during the first 7 days after they were transferred to the iron-free medium in spite of a marked difference in root-associated Fe 3÷-reduction activity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…In spite of the high Fe concentrations found in the upper apical third of citrus rootstock plants from the control and Fe-EDTA treatments (Table 4), those plants exhibited severe iron deficiency symptoms (Table 2), probably because iron was present in the form of non-reactive ferric ion (Fe 3+ ), according to Pérez-Sanz & Lucena (1995), not being easily used in photosynthesis reactions and formation of chlorophyll pigments (Cataldo et al, 1988). Furthermore, Mohammad et Mean followed by the same small letters in the columns and capital letters in the lines do not differ (Scott-Knott test, P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of the high Fe concentrations found in the upper apical third of citrus rootstock plants from the control and Fe-EDTA treatments (Table 4), those plants exhibited severe iron deficiency symptoms (Table 2), probably because iron was present in the form of non-reactive ferric ion (Fe 3+ ), according to Pérez-Sanz & Lucena (1995), not being easily used in photosynthesis reactions and formation of chlorophyll pigments (Cataldo et al, 1988). Furthermore, Mohammad et Mean followed by the same small letters in the columns and capital letters in the lines do not differ (Scott-Knott test, P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Lang et al (1990) observed that the iron extraction in fresh leaves with HCl 1 mol L -1 was a good indicator of the iron status in plants at flowering. Also, Ohwaki & Sugahara (1993) reported that the genotypic differences among Fe-deficient chickpea sensitive and resistant cultivars were attributed to the active iron in leaves grown under iron stress conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In sunflower exposed to iron deficiency, lower leaf chlorophyll concentration was associated with reduction of total iron content (Ranieri et al, 2001). However, several studies have indicated that leaves affected by ferric chlorosis can display total iron contents comparable to those of green leaves (Mehrotra et al, 1991;Ohwaki and Sugahara, 1993). According to Mehrotra et al (1991), it is the high ''active'' iron levels in the mitochondria that confer to some cultivars their aptitude to tolerate iron lack.…”
Section: Discussionmentioning
confidence: 99%
“…In some gates of these areas, it faces some nutrient deficiencies resulting in seed yield losses. One of the most important problems is iron (Fe) deficiency when the susceptible cultivars are grown in the problematic conditions such as in calcareous soil (Gowda and Smithson, 1980;Singh et al, 1986;Ali et al, 1988;Ali et al, 2000;Ohwaki and Sugahara, 1993;Zaiter and Ghalayini, 1994). Seed yield in the cultivated chickpea can reduce by 50% in Lebanon, Syria and India due to Fe-deficiency (Sakal et al, 1987;Ali et al, 2002).…”
Section: Introductionmentioning
confidence: 99%